Beautiful stranger: Voices from the front lines of community practice in Israel. (23rd June 2020) - Feldman, Guy; Frankenburg, Ruth; Bdeer, Rama
Abstract: Over the past few decades, economic, political and cultural forces have altered the development of social policies and affected the life circumstances of oppressed communities in many countries. In response, calls for greater understanding and awareness of macro practice skills and interventions have been increasing within many of the social care professions. These calls have been particularly strong within the social work profession. A major field in macro social work is community practice, which aims to help people organise, plan and act for change. To date, there has been a dearth of studies examining social workers' involvement in community practice at the ground level. Drawing on in‐depth interviews with 26 community social workers in public social services in Israel, this qualitative study examines community social workers' everyday experiences of community practice and the meanings they attribute to it. Findings highlight three main themes: (a) the elusive and unbounded nature of community practice; (b) the tense relations that community social workers maintain with various actors within the profession; and (c) the complex relations they maintain with the communities in which they work. We discuss these findings in light of Georg Simmel's concept of 'the stranger'. Implications to community practice are outlined.